2021
DOI: 10.1088/2043-6254/abde42
|View full text |Cite
|
Sign up to set email alerts
|

Excellent antimicrobial and anti-biofilm activities of Fe–SnO2 nanoparticles as promising antiseptics and disinfectants

Abstract: In recent years, nosocomial infections and antibiotic resistance are major public health problems. Nanotechnology should open new avenues to treat and prevent diseases. In this research work, iron-doped tin dioxide (Fe-SnO2) nanoparticles have been synthesized by the chemical co-precipitation method. X-ray diffraction analysis confirms the formation of nanocrystalline SnO2 single phase with Fe favoring grain growth, the crystallite size increases from 13 up to 29 nm. FT-infrared spectroscopy analysis shows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The mechanism involved in the antibacterial activity of Fe-SnO 2 NPs is assumed to be influenced by the generated reactive oxygen species, viz., H 2 O 2 , superoxide, and hydroxyl radicals, which will penetrate through the bacterial cell membrane, damage DNA, and protein, which will finally inhibit bacterial growth. For Fe-SnO 2 NPs, the increased antibacterial action can be attributed to their smaller particle size, as evidenced by XRD and FESEM analysis, which leads to the generation of a large number of reactive oxygen species on the surface of bacterial cells, resulting in intracellular component leakage and cell death [32, 33]. To check the reliability of the obtained results, a triplicate of the experiment is carried out.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism involved in the antibacterial activity of Fe-SnO 2 NPs is assumed to be influenced by the generated reactive oxygen species, viz., H 2 O 2 , superoxide, and hydroxyl radicals, which will penetrate through the bacterial cell membrane, damage DNA, and protein, which will finally inhibit bacterial growth. For Fe-SnO 2 NPs, the increased antibacterial action can be attributed to their smaller particle size, as evidenced by XRD and FESEM analysis, which leads to the generation of a large number of reactive oxygen species on the surface of bacterial cells, resulting in intracellular component leakage and cell death [32, 33]. To check the reliability of the obtained results, a triplicate of the experiment is carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Obeizi et al [167] reported the antifungal action of Fe-doped SnO 2 NPs against the Candida albicans strain. The microbial activity was checked by agar well diffusion method and after an incubation period of 24 h at 27 • C a ZOI of 23.59 ± 0.22 mm and an MIC of 1 µg mL −1 were observed for the SnO 2 NPs doped with Fe against a ZOI 15.68 ± 0.1 mm for the control sample (gentamicin).…”
Section: Biological Applicationsmentioning
confidence: 99%